Risk Analysis on Organochlorine Pesticides Residue in Potato and Carrot from Conventional and Organic Farms in Citarum Watershed Area, West Java Province, Indonesia - Suphia Rahmawati; Listya Chandra Kirana; Minoru Yoneda; Katharina Oginawati (Jurnal Sains & Teknologi Lingkungan, 2017)
Six samples of carrot and potatoes were collected from conventional and organic farms. Organochlorine pesticides (OCPs) residue was analyzed using liquid-liquid extraction. The concentration of OCPs residue together with the consumption pattern were used to calculate the potential risk. Estimated Daily Intake (EDI) of OCPs residue in carrots and potatoes both from conventional and organic farms were below the standard given in SNI 7313:2008 and the Maximum Residue Limit (MRLs) from USEPA . Hazard quotient (HQ) and Hazard Index (HI) as effect analysis were below the unity, thus there may not be a concern for non-carcinogenic effect. Risk analysis on cancer effects indicated that potatoes samples were above the recommended risk by EPA (10-6). In addition, risk of potatoes samples from organic samples was higher compare to that of the conventional farm. Cancer risk analysis of carrot samples were found below the recommended risk by EPA. Cancer risk effect of carrot samples from conventional farm was slightly higher compare to that of the organic farm.